SINERGITAS PEMERINTAH DESA DAN KOPERASI UNIT DESA (KUD) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA BUMI MAKMUR - Umi Fitriana Lestari; Wendi Aji Saputra (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2025)
This study is determined to see the synergy between the Village Government and the Tuhu Asih Village Unit Cooperative (KUD) in improving community welfare in Bumi Makmur Village, North Musi Rawas Regency. This study employs descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation. Informants of this study consisted of the Village Head, village officials, KUD managers, and the local community. The results indicate that the synergy between the Village Government and KUD is manifested in three main aspects: as motivators, facilitators, and mobilizers. In the motivator aspect, the village government and KUD play a role in providing encouragement, building commitment to cooperation, and encouraging community innovation and creativity. As facilitators, both provide resources such as capital, training, infrastructure, and access to information and technology. Meanwhile, as mobilizers, synergy is demonstrated through increased community participation and coordination in the implementation of village economic programs. This synergy has had a positive impact on increasing community income, the growth of small businesses, and increasing productivity in the agricultural sector. However, improvements are still needed in supporting infrastructure and program sustainability. The conclusion of this study is that effective synergy between the Village Government and the Village Cooperative (KUD) can create sustainable economic empowerment and improve the welfare of the village community as a whole.